2018
DOI: 10.1186/s12864-017-4412-0
|View full text |Cite
|
Sign up to set email alerts
|

No association between ACTN3 R577X and ACE I/D polymorphisms and endurance running times in 698 Caucasian athletes

Abstract: BackgroundStudies investigating associations between ACTN3 R577X and ACE I/D genotypes and endurance athletic status have been limited by small sample sizes from mixed sport disciplines and lack quantitative measures of performance. Aim: To examine the association between ACTN3 R577X and ACE I/D genotypes and best personal running times in a large homogeneous cohort of endurance runners.MethodsWe collected a total of 1064 personal best 1500, 3000, 5000 m and marathon running times of 698 male and female Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 38 publications
5
45
1
1
Order By: Relevance
“…Using a large cohort (n = 346; 555 best personal times) of elite Caucasian athletes with reported running times we identified that ACTN3 577RR individuals had significantly faster running times over 200 m, compared to XX and that the ACTN3 genotype accounted for 0.92% of the difference in sprint speed (Papadimitriou et al, 2016a). However, when the same quantitative approach was used for long distance runners, we found no association between the ACTN3 XX genotype and endurance performance (Papadimitriou et al, 2018), a finding consistent with the majority of case-control studies (Table 2a and…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Using a large cohort (n = 346; 555 best personal times) of elite Caucasian athletes with reported running times we identified that ACTN3 577RR individuals had significantly faster running times over 200 m, compared to XX and that the ACTN3 genotype accounted for 0.92% of the difference in sprint speed (Papadimitriou et al, 2016a). However, when the same quantitative approach was used for long distance runners, we found no association between the ACTN3 XX genotype and endurance performance (Papadimitriou et al, 2018), a finding consistent with the majority of case-control studies (Table 2a and…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Although these findings in West European populations support the hypothesis that the iron-increasing HFE rs1799945 G allele is favorable for endurance performance, replication studies in different ethnic groups using different designs are warranted. This approach leads to the exclusion of false-positive genetic associations (Eynon et al 2013;Zarebska et al 2017;Papadimitriou et al 2018;Yvert et al 2018;Guilherme et al 2019;Pickering et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-actinin-3 has been associated with alterations of the contractile properties of the sarcomere in type II muscle fibers [16], effects on the differentiation of muscle fiber type or hypertrophy through indirect interactions between alpha-actinin-3 and signaling proteins such as calcineurin [37], alterations of the ability to resist and/or recover from muscle damage caused by exercise [27], changes to the metabolic profile of muscle fibers through altered interactions with metabolic enzymes [18], and improved glycogen consumption or signaling for muscle hypertrophy [25]. None of these scenarios is exclusive of any other, and the actual mechanism is likely to be a combination of several of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The genotype that does not express alpha-actinin-3 (ACTN3-XX) has been linked to activities with a predominance of aerobic endurance [1,4,5,13,35]. Nonetheless, a recent multi-cohort quantitative analysis demonstrated that it is unlikely that the ACTN3-XX genotype provides an advantage in competitive endurance running performance [27].…”
Section: Introductionmentioning
confidence: 99%